2021
DOI: 10.1021/acsomega.1c00008
|View full text |Cite
|
Sign up to set email alerts
|

Optical Detection of CoV-SARS-2 Viral Proteins to Sub-Picomolar Concentrations

Abstract: The emergence of a new strain of coronavirus in late 2019, SARS-CoV-2, led to a global pandemic in 2020. This may have been preventable if large scale, rapid diagnosis of active cases had been possible, and this has highlighted the need for more effective and efficient ways of detecting and managing viral infections. In this work, we investigate three different optical techniques for quantifying the binding of recombinant SARS-CoV-2 spike protein to surface-immobilized oligonucleotide aptamers. Biolayer interf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 48 publications
(78 reference statements)
1
49
0
Order By: Relevance
“…The specific biosensor has then been built on an SPR in POFs device and optical measurements confirmed the specific protein binding in a nanomolar range. The obtained ability to detect the SARS-CoV-2 Spike protein in the nanomolar range is similar to that recently achieved exploiting a similar bio-receptor on an SPR conventional probe [ 48 ] and a similar SPR platform in POFs combined with a specific MIP receptor layer [ 49 ].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The specific biosensor has then been built on an SPR in POFs device and optical measurements confirmed the specific protein binding in a nanomolar range. The obtained ability to detect the SARS-CoV-2 Spike protein in the nanomolar range is similar to that recently achieved exploiting a similar bio-receptor on an SPR conventional probe [ 48 ] and a similar SPR platform in POFs combined with a specific MIP receptor layer [ 49 ].…”
Section: Discussionsupporting
confidence: 78%
“…Our limit of detection is not so far from that published by Stanborough and coworkers, who using our same aptamer sequence on a standard SPR instrument, observed that 5 nM spike protein can be clearly distinguished from the baseline [ 48 ]; however, they used a conventional SPR instrument where instrument setup and microfluidic are well optimized and also a different chemistry based on thiols.…”
Section: Resultsmentioning
confidence: 88%
“…RT-PCR tests can detect the smallest amounts of virus RNA in the acute phases, but fail to distinguish between infectious or non-infectious virus. In addition, sample preparation is not trivial and requires advanced infrastructure and resources [ 110 , 111 ]. Serological tests on the other hand, such as ELISAs, can only detect antibodies that are present in the later stages of the infection.…”
Section: Aptamer Applications In Coronavirus Diseasesmentioning
confidence: 99%
“…are present, paper sensors can be functionalized with specific recognition elements (e.g., proteins, antibodies, aptamers) for specific binding and detection [ 4 ]. Recently, SARS-CoV-2 spike proteins were detected at the ∼ 250 nM level by applying 10 μL of sample to oligonucleotide aptamers and Ag colloids immobilized onto polytetrafluoroethylene (PTFE) membrane filters [ 43 ]. In addition, Au coated polyethylene naphthalate (PEN) polymer substrate have been modified with aptamer DNA for detection of influenza A H1N1 virus at a 97 PFU/mL detection limit [ 44 ].…”
Section: Sers Based Sensingmentioning
confidence: 99%